Prevention of intraoperative bleeding during thoracoscopic left lower lobectomy; an unnecessary occlusion of pulmonary artery and vein - Dario Amore; Marcellino Cicalese; Umberto Caterino; Dino Casazza; Pasquale Imitazione; Cristiano Cesaro (Annals of Thoracic Medicine)
Complicated hilar anatomy may be technically challenging for thoracic surgeons, especially during video-assisted thoracic surgery lobectomy. In such instances, to prevent hemorrhagic complications and conversion to open thoracotomy, several methods of proximal and distal vascular control have been proposed. Here, we present a technique of unnecessary occlusion of the main pulmonary artery and preserved pulmonary vein during a challenging thoracoscopic left lower lobectomy in patient with lung cancer and interlobar lymphadenopathy.